2016
DOI: 10.1177/1476127016651001
|View full text |Cite
|
Sign up to set email alerts
|

Corporate political activity, public policy uncertainty, and firm outcomes: A meta-analysis

Abstract: Although significant scholarship has been devoted to the study of corporate political activity, contradictory messages emerge regarding its impact on public policy outcomes and firm performance. Using meta-analytic methods on a US-only sample of 93 studies, working papers, and books, we try to disentangle two mechanisms that explain why corporate political activity is not always beneficial to firms: (1) the uncertainty about the public policy process itself, that is, can firms get the policies they want throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 167 publications
(150 reference statements)
1
73
0
2
Order By: Relevance
“…First, I provide an answer to a question that has vexed scholars: explaining why firms engage in CPA in the first place. For some time, scholars have struggled with this question, particularly in light of findings that there was no relationship between CPA and firm performance (Hadani, Bonardi, & Dahan, 2017;Hadani & Schuler, 2013). In effect, I have alluded that CPA needs to be divided into two groups, each with its own motivation.…”
Section: Review Of Resultsmentioning
confidence: 99%
“…First, I provide an answer to a question that has vexed scholars: explaining why firms engage in CPA in the first place. For some time, scholars have struggled with this question, particularly in light of findings that there was no relationship between CPA and firm performance (Hadani, Bonardi, & Dahan, 2017;Hadani & Schuler, 2013). In effect, I have alluded that CPA needs to be divided into two groups, each with its own motivation.…”
Section: Review Of Resultsmentioning
confidence: 99%
“…Doh et al, 2012). Some research indicates that CPA has conditionally influence on a firm's efficiency (Hadani, Bonardi, & Dahan, 2017), and other suggest that CPA is recognized as a nonmarket strategy that 'attempts to shape government policy in ways favorable to the firm' (Hillman, Keim, & Schuler, 2004, p. 838).…”
Section: Corporative Political Activities As a Part Of The Company's mentioning
confidence: 99%
“…In this research, this study has explored the concept of organizational behavior, which explains that the CPA is a significant element of the zero-sum political game that cannot be perfectly assessed. This suggested that the CPA cannot significantly improve the FP (Hadani and Schuler 2013;Hadani et al 2017;.…”
Section: Effect Of the Cpa On Fpmentioning
confidence: 99%
“…This study measured CPA as some organizational non-market operations that consist of any one of the given operations: PAC donations and lobbying expenses (Hadani et al 2017). The lobbying expenditure records and the PAC were acquired from the CRP (Centre for Responsive Politics) at the US Senate website, which has been giving organizational expenses on lobbying operations on a tri-monthly basis since 1999.…”
Section: Measurement Of Corporate Political Activitymentioning
confidence: 99%